Edukasi Anemia dan Kekurangan Energi Kronik (KEK) Pada Remaja Putri di Kota Metro - M Ridwan; Firda Fibrila (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
Health problems that commonly occur in young women today are related to nutrient intake. Young women or women of childbearing age tend to experience malnutrition (calories and protein) that lasts for a long time or is chronic. This condition causes adolescents to have poor nutrition, chronic lack of energy, lack of protein energy including anemia. Cases of anemia in young women reach 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. In addition, nationally, the prevalence of chronic energy deficiency (CED) in young women (aged 15-19 years) has increased. In 2018 CED cases were 33.5% and in 2020 it was 36.3%. This community service activity aims to provide education to 240 young women in Metro City, as well as assess their knowledge about anemia and CED. The activity method starts from situation analysis, socialization, implementation of pretest, education and posttest, then evaluation and reflection. The results of this activity have an impact on increasing the understanding of young women about the dangers of Anemia and CED.